Impact of two-photon absorption and free-carrier effects on time lens based on four-wave mixing in silicon waveguides. (11th July 2018) - Xie, Peng; Sun, Qibing; Wang, Leiran; Wen, Yu; Wang, Xinyu; Wang, Guoxi; Zeng, Chao; Liu, Mulong; Ge, Zhiqiang; Lu, Zhizhou
Abstract: We investigate the influences of two-photon absorption (TPA) and free-carrier effects on a time lens via four-wave mixing in silicon waveguides. It is found that the output waveform is severely modulated and the conversion efficiency is sharply reduced in temporal imaging owing to the impacts of the nonlinear absorption. A silicon–organic hybrid slot waveguide with negligible TPA is proposed for the time lens, which could realize 600× magnification of femtosecond pulses. These results can increase the signal bandwidth from gigahertz to terahertz and give rise to important potential applications for ultrafast optical signal processing in integrated optics, ultrafast optics, and optical communications.